ENGLISH FOR LAW: ANALYSIS OF ENGLISH LANGUAGE REQUIREMENTS FOR SPECIAL PURPOSE AT THE FACULTY OF LAW, UNIVERSITY OF NAHDLATUL ULAMA INDONESIA - Chyta Anindhyta (AL WASATH Jurnal Ilmu Hukum, 2022)
The fast flow of globalization that is currently being hit by Indonesia cannot be avoided. This brought a change in the development of English for Specific Purposes. Responding to these conditions, this research was conducted to find out an analysis of the needs of ESP in the Faculty of Law, which will continue with what kind of material is needed, especially for law students, as well as ESP supporting modules and media. This research focuses on the perspective of undergraduate students at the Faculty of Law. This research is focused on Law Faculty students at a university in DKI Jakarta, Indonesia using a mixed research design (mix method). Data were obtained from several techniques, namely interviews, documentation and questionnaires. Based on the interview data, it was found that the expected material for ESP at the Faculty of Law was communication skills, especially speaking and writing to prepare themselves to serve their clients later. In addition, the existence of modules and media on grammatical discussions and pronunciation exercises that are less interesting needs to be followed up with the development of supporting modules and media so that learning activities can be packaged in a more active and interesting way. From some of the explanations above, it is necessary to develop teaching materials, modules and supporting media for the Faculty of Law.